Peningkatan Kesadaran Hukum Kesehatan melalui Edukasi Partisipatif Pasca UU No. 17 Tahun 2023 di Desa Kadubelang, Pandeglang: Enhancing Health Law Awareness through Participatory Education Following Law No. 17 of 2023 in Kadubelang Village, Pandeglang - Agus Ardinansyah; Mochammad Atmaji Windrianto; Irfan Islami (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Legal awareness regarding patient and healthcare provider rights and obligations remains low, particularly in rural areas of Indonesia. The enactment of Law No. 17 of 2023 on Health has reshaped the legal framework governing patient-healthcare relations, highlighting the need for community education. This community service project aimed to enhance both the public's and healthcare professionals' understanding of their rights and responsibilities under the new law while promoting a participatory health law culture. A participatory approach was employed through interactive lectures, focus group discussions, and the distribution of an educational booklet titled "Rights and Obligations in Healthcare Services." Evaluations using pre- and post-tests and in-depth interviews demonstrated that participants' legal knowledge improved from 42.3% to 85.7%, awareness of patient rights violations increased by 58%, and understanding of professional accountability among healthcare workers rose by 61%. These findings indicate that community-based legal education effectively enhances legal literacy and fosters stronger ethical and legal relationships between patients and healthcare providers.